Orientalist representations of Asians in American rock music videos by Linkin Park and Thirty Seconds to Mars - Weerawat Lertromyanant (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study aims to investigate the representations of Asians in American rock music videos by Linkin Park and Thirty Seconds to Mars, which were produced and released from 2000 to 2010. The study employs the critique of Orientalism proposed by Edward Said in the analysis of the music videos. According to Said, Orientalism refers to the ways in which the West constructs the East based on the binary opposition between the Occident and the Orient. Furthermore, this study makes use of visual and non-verbal communication assessment techniques in order to examine and disclose Orientalist views and assumptions in the music videos. The results of this study reveal that, although all the music videos appear in the form of disjuncture in which visual images have no relationship with the lyrical content, the representations of Asians, as depicted in the music videos, clearly reinforce Orientalist assumptions in which Asians are fundamentally portrayed in correspondence with the Oriental stereotypes that associate Asians with mystery, backwardness, irrationality, barbarism, sensuality, and passivity. Besides, Asian cultures are misrepresented and also seem to be used as a tool to contribute to the negative depictions of Asians. Lastly, the different representations of Asian characters and Western characters clearly demonstrate the binary opposition drawn between the (superior) West and the (inferior) Orient.